THERMAL AGING STUDY OF BIODEGRADABLE POLYMER MATERIALS BY DIELECTRIC THERMAL ANALYSIS - Aleksandra Porjazoska Kujundziski; Dragica Chamovska (Journal of Engineering & Processing Management, 2015)
Two different studies of the thermal aging of polyesters based on lactic and glycolic acidswere compared. Thermal degradation of poly(L-lactic acid) (PLLA), poly(L-lactic acid-co-glycolicacid) (PLLGA) and poly(DL-lactic acid-co-glycolic acid) (PDLGA) was studied by the dielectricthermal analysis (DETA). The aging was performed at 37C in vacuum oven. The dielectric featuresi.e., dielectric permittivity,ε', dielectric losses,ε'', and phase lag, tg δ, were determined by PL-DETAcontaining a parallel plate capacitance cell, from the room temperature to 80 ℃, 150 ℃, and 180 ℃,at the heating rates of 2 and 3 ℃min-1. Dielectric scans were obtained at a frequency of 1 kHz anda.c. signal of 200 mV. Different behavior of PLLA, PLLGA, and PDLGA during degradation wasobserved. As the aging of PDLGA proceeds, dielectric losses shift to the lower temperatures,indicating existence of lower molecular weights. ε' - T, and tg δ - T dependences of PLLGA, as wellas those for PLLA show two simultaneous processes occurring, crystallization and degradation.
Keywords: poly(L-lactic acid); poly(L-(or DL-) lactic-co-glycolic acid); thermal aging; dielectric thermal analysis